Efecto de la testosterona sobre el desarrollo de las espículas peneanas en cobayos (cavia porcellus) destinados para reproductores. - Noroña Ramírez, Verónica Lourdes (2020)
This research determined the influence of testosterone on spinal growth in guinea pigs (Cavia porcellus). Sixteen males in puberty of approximately three months used with a weight of 800 to 1000 grams of conformation of Type A and coat type 1, which were separated at random in groups of four. Under the same conditions of feeding and maintenance, they are conserving a control group (T0) and three experimental ones (T1, T2, T3). The others were inoculated only once with Testosterone Undecanoate (exogenous testosterone), which inoculated with three doses in milligrams of 8(T1), 12(T2), and 16(T3) intramuscularly which formed a deposit where the drug was to be released gradually over time. Before inoculation, a blood sample was taken through the cardiac puncture, and the spicular size was measured in millimeters every seven days during thirty days, to observe the growth and compare the treatments wherein the fifth observation the T3 results in the mean of 0.43 being the highest value compared to T0 with a mean of 0.3; until the fifth observation, the next blood sample is taken to measure testosterone. Therefore, it concluded that testosterone influences spicular development.